LAYER ROTATION AROUND VERTICAL FAULT OVERLAP ZONES: OBSERVATIONS FROM SEISMIC DATA, FIELD EXAMPLES, AND PHYSICAL EXPERIMENTS - Rykkelid E.; Fossen H. (My University, 2002)
Vertically overlapping fault segments are common structures in faulted hydrocarbon reservoirs. Experimental work and field observations show a close relationship between the rotation of layers in the region of overlap, the type of overlap (restraining vs. releasing) and fault curvature. In general, releasing overlap zones (where the normal fault steps upward into the hanging-wall) show normal rotation or drag, thus decreasing the effective throw on the fault. In contrast, restraining overlaps tend to develop reverse rotation in the overlap zone, particularly if the normal fault tips curve toward each other. Releasing overlap zones seem to be more common than the restraining zones, and the overlaps tend to form in shaly layers between thicker sandstones. Narrow overlaps of this type typically develop zones of drag or shale smear that could seal or reduce communication across the adjacent sandstone layers. Hence, overlap zones may significantly influence communication in a reservoir, depending on the fault arrangement, geometry, and lithological properties. Seismic interpreters and structural geologists should pay particular attention to layer rotation to identify vertical overlap structures and to evaluate their influence on reservoir performance.
Keywords: FAULT OVERLAP ZONES; FAULT SEALING; DRAG